HUBUNGAN GANGGUAN ANSIETAS TERHADAP PENINGKATAN KADAR KOLESTEROL PADA PASIEN ANSIETAS YANG BEROBAT JALAN DI RSU MADANI MEDAN - ELVIANI .; NANDA SARI NURALITA; ELMEIDA EFFENDY; ISRA THRISTY (JURNAL ILMIAH MAKSITEK, 2021)
Anxiety is the most common psychiatric disorder. Overeating due to the response to anxiety disorders can cause an increasein total cholesterol and LDL levels. To determine the relationship between anxiety disorders and increased cholesterol levelsin anxiety patients who treatment at the RSU. Madani. This study use cross sectional study design. The sampling techniqueuse non-probability sampling. The examination was carried out using an easy-touch cholesterol level check tool.The number of samples used was 41 respondents with anxiety disorders, then an analysis test was performed using theKruskal-Wallis test. The Kruskal-Wallis test results showed that there is a relationship between anxiety disorders andincreased cholesterol levels in patients with anxiety disorders with a value of p = 0.001 (p <0.05). Anxiety disorders of asevere degree can raise cholesterol levels. There is a relationship between anxiety disorders and increased cholesterollevels in patients with anxiety disorders.